RELATIONSHIP OF FOVEA PALATINI TO VIBRATING LINE IN PATIENTS AT A TERTIARY CARE HOSPITAL (Journal of Medical & Health Sciences Review, 2025)
Background: The posterior palatal seal is essential for the retention and stability of maxillary complete dentures. The fovea palatini and the vibrating line are critical anatomical landmarks used to determine the denture's posterior extent. However, variability in their spatial relationship across populations may affect the accuracy of denture border placement. Limited data exist from South Asian populations, particularly in clinical settings, regarding this anatomical relationship.Objective: To evaluate the positional relationship between the fovea palatini and the vibrating line in a sample of patients at a tertiary care dental hospital and to assess its association with age and gender.Methods: A descriptive cross-sectional study was conducted over six months at the Department of Prosthodontics, Bacha Khan College of Dentistry, Mardan. A total of 151 patients aged 20–80 years with visible fovea palatini and normal palatal mucosa were included using consecutive non-probability sampling. The vibrating line was identified using the phonation method and recorded relative to the fovea palatini as anterior, coinciding, or posterior. Associations with age and gender were analyzed using Chi-square tests. Data were processed using SPSS version 25, and a p-value of